Self-Efficacy dan Locus of Control terhadap Kinerja Karyawan pada PT BRI Corporate University Campus Padang - Maria Magdalena; Rahmatul Hijri (ARZUSIN, 2025)
Psychological factors such as self-efficacy and locus of control play a crucial role in enhancing employee performance; however, there remains a research gap regarding the significant influence of these variables within the context of educational and training organizations. This study aims to analyze the influence of self-efficacy and locus of control on employee performance at PT BRI Corporate University Campus Padang. A quantitative approach was employed using a saturated sampling technique (census), involving the entire population of 50 employees as respondents. Data were collected through questionnaires based on validated indicators for each variable and analyzed using validity and reliability tests, followed by multiple linear regression with SPSS version 23. The results show that self-efficacy has a positive and significant effect on employee performance (t-value = 3.120 > t-table = 1.677; sig. = 0.003 < 0.05), as does locus of control (t-value = 7.699 > t-table = 1.677; sig. = 0.000 < 0.05). The study concludes that higher levels of self-efficacy and internal locus of control are associated with better employee performance. These findings offer strategic implications for human resource development, particularly in strengthening psychological factors to support optimal performance within learning-oriented organizations.